Exposição crônica ao chumbo aumenta a pressão arterial e reduz a reatividade pressórica em ratos - Rozetti, Cindy Medici Toscano (2015)
Lead has been associated as one of risk factors for the development of hypertension and other cardiovascular diseases. Our purpose was to investigate whether the effects of chronic exposure to low concentrations of lead on arterial pressure and pressure reactivity and to elucidate mechanisms involved in these changes. Male Wistar rats were sorted randomly into two groups: control (Ct) and treatment with 100 ppm of lead (Pb) added to drinking water for 30 days. Systolic blood pressure (SBP) was measured weekly. Following treatment, SBP, diastolic arterial pressure (DBP) and heart rate (HR) were measured. Treatment increased arterial pressure and decreased the pressure reactivity to phenylephrine. Putative roles of the renin angiotensin system and the autonomic reflexes in these changes were also evaluated. AT1 receptor blocker (losartan, 10 mg/Kg) reduced the increase of arterial pressure and the ganglionic blockade (hexamethonium, 20 mg/Kg) was able to reduce SBP, DBP and HR. These results suggests that there is a participation of the renin angiotensin system and an increase in sympathetic activity, respectively, caused by lead. Isoproterenol increased left ventricular systolic pressure (LVSP), end-diastolic pressure (LVEDP) and HR only in the control group suggesting the existence of a modulated activity of β1-adrenoceptors which was confirmed by Western Blot analyses. Moreover, indomethacin (0,1 mg/kg, IV) reduced SBP and DBP from Pb group. L-NAME (3mg/kg, IV) increased SBP and DBP in both groups, however, the magnitude of the effects in the control group were higher than those of the Pb group. These results propose the involvement of cyclooxygenase (COX) activity and reduced bioavailability of nitric oxide (NO) in these changes respectively. Decreased pressure reactivity may be associated to alteration of endothelial modulation mediated by the COX activity and reduced bioavailability of NO. These findings offer further evidence that chronic exposure to lead even at low concentrations can trigger mechanisms for hypertension development and might be an environmental risk factor for cardiovascular disease. Results presented here provide guidance for reviewing the lead concentrations considered to be safe.